Phytochemical screening of selected Xerophytes of Ramdurg region of Belgavi District Karnataka State - Kamath, A D (International Journal of Pharmaceutical & Biological Archive, 2016)
Phytochemical screening of selected Xerophytes of Ramdurg region of Belgavi District Karnataka State